The moderating role of social capital for late-career management intervention effects on older employees' work engagement - Jokisaari, Markku (Wiley, 2025)
Despite increasing interest in supporting older workers' motivation, retention, and well-being at work, knowledge about how social networks at work may affect the efficacy of training interventions among older employees is scarce. These social ties are an important source of resources for older workers' careers. This study examined the characteristics of older workers' personal social networks as boundary conditions for the effects of late-career management intervention on work engagement. Data were used from an earlier randomized controlled trial (RCT) in which senior employees (mean age of 58 years) participated in a peer group-based training intervention and were asked to complete follow-up surveys at baseline, post-intervention, and after 6 months (Vuori et al., 2019, Journal of Vocational Behavior, 115: 103327). The results showed that older workers' social ties at higher organizational levels (upper reachability) and the number of social ties at work moderated the effect of the intervention on work engagement. Specifically, the intervention aimed at enhancing employees' personal resources improved work engagement for senior employees with few or no social ties at work with whom they could discuss important matters, and for those with social ties at higher organizational levels. However, the relationship quality between older workers and their leaders showed no moderation effect. This study encourages human resources professionals to consider the social network characteristics and peer learning of older workers when providing training to enhance their work engagement.